A comparison between fixed and random sampling of a low density spotted bass population in a large river. Issue 1 (1st January 2019) - Boone, Evan C.; Meiners, Scott J.; Frankland, Leslie D.; Laursen, Jeffrey R.; Colombo, Robert E.
Abstract: Characterizing the structure of riverine fish populations that are patchily distributed and at low densities is often difficult. Due to the wide distribution but low abundance of Spotted Bass, Micropterus punctulatus, throughout the lower Wabash River (LWR), captures from fixed and random sampling designs were compared to assess their performance in determining relative abundance and size structure. The LWR is monitored using both sampling regimes—the Long Term Electrofishing Program monitors community assemblages uses a stratified-random sampling, whereas the Illinois Department of Natural Resources monitors the fish community using a fixed-sampling design. Mean CPUE was significantly higher for fixed site sampling compared to random sites. However, the size structure of Spotted Bass sampled by each design were similar. These results suggest random-sampling designs should be used when monitoring low density populations of fishes in large riverine systems because this method provides the greatest spatial coverage of habitats, evaluates heterogeneity in distribution, and provides a representative measure of abundance throughout an entire aquatic system. In situations where size distribution or temporal trends are the only goal, fixed site sampling would be sufficient.